167k views
11 votes
Solve the inequality


what is the solution?

Solve the inequality what is the solution?-example-1
User McLan
by
4.7k points

1 Answer

5 votes

Answer:

The solution to the inequality is:


2\ge (g)/(-4)\quad :\quad \begin{bmatrix}\mathrm{Solution:}\:&\:g\ge \:-8\:\\ \:\mathrm{Interval\:Notation:}&\:[-8,\:\infty \:)\end{bmatrix}

Please also check the graph of the solution to the inequality.

Explanation:

Given the inequality


2\ge (g)/(-4)

switch sides


(g)/(-4)\le \:2

Multiply both sides by -1 (reverse the inequality)


(g\left(-1\right))/(-4)\ge \:2\left(-1\right)

Simplify


(g)/(4)\ge \:-2

Multiply both sides by 4


(4g)/(4)\ge \:4\left(-2\right)

Simplify


g\ge \:-8

Therefore, the solution to the inequality is:


2\ge (g)/(-4)\quad :\quad \begin{bmatrix}\mathrm{Solution:}\:&\:g\ge \:-8\:\\ \:\mathrm{Interval\:Notation:}&\:[-8,\:\infty \:)\end{bmatrix}

Please also check the graph of the solution to the inequality.

Solve the inequality what is the solution?-example-1
User Sairaj Sawant
by
5.2k points